2015
DOI: 10.1063/1.4906782
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of critical current density in YBa2Cu3O7 films using a semiconductor ion implanter

Abstract: An up-to-11-fold enhancement was observed in the in-magnetic-field critical current density (J c ) in epitaxial YBa 2 Cu 3 O 7 films on CeO 2 -buffered SrTiO 3 substrates by irradiation with 200-to 750-keV Si and 200-keV B ions. This enhancement indicates that ion beams in the range of 100 to 1000 keV, which are widely used for modifying the conductive properties of semiconducting materials, can significantly improve the vortex-pinning properties in second-generation superconducting wires. Also observed was a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
21
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 32 publications
3
21
0
2
Order By: Relevance
“…Some of the earlier irradiation studies were carried out on YBCO films with no Ag coating or at most an extremely thin layer [9]. However, studies have shown that the post annealing of the samples at temperatures above 300 o C essentially removes the defects from the YBCO film.…”
Section: B Short Sample Irradiationmentioning
confidence: 99%
“…Some of the earlier irradiation studies were carried out on YBCO films with no Ag coating or at most an extremely thin layer [9]. However, studies have shown that the post annealing of the samples at temperatures above 300 o C essentially removes the defects from the YBCO film.…”
Section: B Short Sample Irradiationmentioning
confidence: 99%
“…Their effect on vortex pinning in superconductors as diverse as HTS single crystals and epitaxial films [19][20][21][22][23][24][25] and Fe-based superconductors [26,27] has been extensively studied. However, only recently has their potential for improving the performance of commercial coated conductors been explored [28][29][30][31][32][33][34][35]. In particular, in our previous work [29] we have demonstrated that the in-field critical current density of short samples cut from production-line coated conductors can be doubled using irradiation with 4 MeV protons.…”
mentioning
confidence: 99%
“…In this article, we explore the case of monodisperse spherical defects with the size of a few coherence lengths which model nanoparticles in coated YBCO conductors. In addition, similar pinning centers in the form of impurity clusters can be introduced by proton irradiation which provides an opportunity for further enhancement of the critical current [10,11].…”
mentioning
confidence: 99%